Assessing the Impact of Skin Tone on Tooth Shade Selection: A Cross-Sectional Study - Priyanka Rai; Gattu Anusha; Kiran Kunwar Rathore; Vimal Kumar; K. Rajitha Reddy; Sanjana Kodati (Journal of Pharmacy and Bioallied Sciences)
Background: The role of skin tone in determining tooth shade preferences is crucial in aesthetic dentistry. This study aims to evaluate the impact of skin tone on tooth shade selection by comparing preferences between dental professionals and laypersons. Methods: A cross-sectional study was conducted with 100 participants, including 50 dental specialists (prosthodontists and endodontists) and 50 laypersons (teachers, engineers, and business owners). Participants were presented with a randomized slideshow of 15 modified images featuring a woman with varying skin tones (fair, medium, dark) and tooth shades (from 00 to 04). Each image was rated on a scale from 1 (Very unattractive) to 4 (Very attractive). Results: There were no statistically significant differences in the ratings of dental appearance across different skin tones between dental professionals and laypersons. For fair skin, medium skin, and dark skin tones, the mean scores assigned by both groups were statistically indistinguishable (P > 0.05). Conclusion: The study indicates that both dental professionals and laypersons converge in their tooth shade preferences related to skin tone, despite their different backgrounds. This suggests a shared perspective on dental aesthetics and highlights the importance of aligning aesthetic treatments with general preferences.